The methyl-CpG-binding protein MeCP2 and neurological disease. (22nd July 2008) - Bird, Adrian
Abstract : The methyl-CpG-binding protein MeCP2 was discovered over 15 years ago as part of a search for proteins that selectively bind methylated DNA. It is a nuclear protein that is largely chromatin-bound and has a strong preference for binding to methylated DNA sequences in vivo . Evidence from model systems shows that MeCP2 can recruit the Sin3a co-repressor complex to promoters leading to transcriptional repression, therefore suggesting that MeCP2 can interpret the DNA methylation signal to bring about gene silencing. Mutations in the human MECP2 gene cause the autism spectrum disorder Rett Syndrome. MeCP2 is most highly expressed in neurons, and mice lacking this protein show symptoms that strikingly parallel those of Rett patients. Surprisingly, these symptoms are efficiently reversed by delayed activation of a 'stopped' Mecp2 gene, raising hopes that human Rett syndrome may also be reversible. Future studies of MeCP2 promise to shed light upon brain function, neurological disease and the biology of DNA methylation.